Dehydroepiandrosterone Supplementation Improves the Outcomes of in vitro Fertilization Cycles in Older Patients With Diminished Ovarian Reserve - Chen, San-Nung; Tsui, Kuan-Hao; Wang, Peng-Hui; Chern, Chyi-Uei; Wen, Zhi-Hong; Lin, Li-Te (Frontiers in Endocrinology, 2019)
Background: Dehydroepiandrosterone (DHEA) supplementation has been reported to have beneficial effects on the in vitro fertilization (IVF) outcomes of patients with poor ovarian response or diminished ovarian reserve. The Patient-Oriented Strategies Encompassing IndividualizeD Oocyte Number (POSEIDON) stratification is a set of newly established criteria for low prognosis patients. The aim of this study was to examine the potential effects of DHEA supplementation on the IVF outcomes of patients who fulfill the POSEIDON group 4 criteria. Methods: This retrospective cohort study investigated 297 cycles that fulfilled the POSEIDON group 4 criteria and underwent IVF treatment using the gonadotropin-releasing hormone antagonist protocol. The study group contained 159 cycles that received DHEA (30 mg three times per day) daily for 12 weeks before their IVF cycles. The control group included 138 cycles that underwent IVF cycles but did not receive DHEA. The baseline characteristics and cycle parameters as well as the IVF outcomes of both groups were compared. Results: In terms of baseline characteristics, more previous IVF attempts and lower AMH levels were found in the study group than in the control group. Regarding IVF outcomes, patients in the study group had significantly higher follicular oocyte index and higher numbers of retrieved oocytes, metaphase II oocytes, fertilized oocytes, day-3 embryos and top-quality day-3 embryos than those in the control group. Besides, a higher cumulative pregnancy rate and lower cancellation rate were observed in the study group than in the control group although clinical pregnancy rate, live birth rate and cumulative live birth rate did not differ between the two groups. Whether patients are aged ≤ 40 years or aged > 40, higher numbers of oocytes and embryos were observed in the study group than in the control group. In patients aged > 40, cumulative pregnancy rate was significantly higher in the study group than in the control group. Conclusions: Our data suggest that DHEA supplementation might increase both oocyte and embryo yields, as well as cumulative pregnancy rates, in patients fulfilling the POSEIDON group 4 criteria.